The Role of Customer Satisfaction in a Relation of Experiential Marketing and Customer Loyalty - Nurcahyo, Bagus (Advances in Social Sciences Research Journal, 2016)
The purpose of the research is to know if there is any influence from the element of experiential marketing to the customer’s satisfaction and the influence of customer’s satisfaction in their loyalty. 200 students collage involve in this research as respondent. Hypothesis testing used is path analysis. The result of the research shows that customer satisfaction has no role in the relation of experiential marketing and costumer loyalty.